Master teachers' perceptions of their competence level and difficulties in conducting research - Azucena, Maricel A (University of the Philippines Visayas, 2018)
This study is an inquiry on master teachers' practice of research within the academe and it underscores their self-perceived competence level and difficulties in doing research. This study is also suggestive of the importance of attaining competence and addressing specific difficulties before carrying out any research endeavor. The study utilized thirty master teachers from public secondary schools in the ALEOSAN district, Iloilo who were available for testing during the second semester of SY 2016-1017. A researcher-made instrument was used to determine the competence level and difficulties of the respondents in doing research. The quantitative-qualitative (mixed) method of research was employed in this study. Quantitative data were analyzed using the means, standard deviation, and the Mann-Whitney U-test and Kruskal-Wallis P-test for comparisons of group means set at .05 alpha level of significance. Qualitative content analysis was employed by the researcher in evaluating data gathered through the written interview. Results revealed that master teachers have an above average level of competence in applying research theories into practice and they have a positive attitude towards undertaking research activities ; but are rather deterred by prevalent difficulties such as the lack of library resources, lack of financial resources, absence of expert help, lack of technology, and research as aa non-priority in their conduct of research. Further suggestions in improving master teacher's competence and addressing hindrances in doing research discussed.